PENGEMBANGAN SISTEM INFORMASI PREVENTIVE MAINTENANCE PADA PT. MEDAN TROPICAL CANNING - Erikson Damanik (Politeknik Bisnis Indonesia, 2019)
PT. Medan Tropical Canning is a company engaged in the production and export of aquaculture materials and marine catches, such as shrimp, fish, and so on. PT. Medan Tropical Canning manually monitors and maintains production machinery such as calculation of maintenance schedules and replacement of spare parts contained in production machinery. Frequent occurrences of errors in the calculation of maintenance scheduling and replacement of spare parts cause disruption of production activities.To deal with the problem, the authors propose a computerized information system using the STRADIS system development methodology. This information system is a program developed using the Microsoft Visual Basic 2005 programming language, database using Microsoft SQL Server 2000, and Business Objects Crystal Report 10 for report design.With the completion of the developed system, the data inputted will be processed with a database management system so that it can help monitor and maintain production machines and make reports faster and more accurate. The results of this computerized preventive maintenance information system are expected to benefit the company.